The Effect of Dietary Supplement Coriander Seed on Abdominal Fat Deposition and Fatty Acid Composition in Japonese Quail (A) - Ertas, Osman Nihat (Medwell Online, 2013)
An experiment was conducted to evaluated the effect of dieatary supplemented coriander seed on fatty acid composition of abdominal fat and abdominal fat deposition in quails. A total of 490, 3 days old (49 males and 49 females) Japanase quails (Coturnix Coturnix Japonica) were randomly divided into five trial groups in each group according to diets, in the control group. Four different levels of coriander seeds 0.5% coriander group, 1% coriander group, 2% coriander group and 4% coriander group were added to the basal diets. Fatty acid profiles for abdominal fat were altered by added coriander seeds in diets. Total PUFA was higher 4%, 2% coriander seed according to 0.5%, 1% and control groups (p<0.01). In conclusion because of hypolipidemic and antioxidative properties of coriander, addition of 2-4% of coriander seed into quail diets significantly reduced SFA, abdominal fat deposition and increased PUFA (especially Omega-3 levels) in abdominal fat (p<0.01).
Keywords: Japanase quail; coriander sativum; fatty acids; abdominal fat; seeds